Analisis Karakteristik Kurikulum Nasional dalam Sistem Pendidikan di Indonesia - Ayani Filko; Desi Purnama Sari (Lembaga Intelektual Muda (LIM) Maluku, 2026)
This study aims to analyze the characteristics of the national curriculum in the Indonesian education system through a literature study approach. The study uses a qualitative method with a library research type that utilizes various scientific sources in the form of books, journal articles, government regulations, and educational policy documents related to the national curriculum, specifically the Independent Curriculum. Data collection techniques are carried out through documentation studies by tracing, selecting, classifying, and recording sources relevant to the research focus. The data obtained are analyzed using content analysis through the stages of data reduction, data presentation, and drawing conclusions. The results show that the main characteristics of the national curriculum in Indonesia include orientation towards national education goals, based on national education standards, flexible and adaptive to developments in science and technology, and student-centered. In addition, the Independent Curriculum emphasizes competency and character development through the Pancasila Student Profile, project-based learning, differentiated learning, and authentic assessment, thus creating learning that is more meaningful, contextual, and relevant to the needs of the 21st century.